Challenges and opportunities in development sustainable transportation system in Saudi Arabia - Dahim, M A (ASCEE, 2023)
This paper presents the recent development of transportation system in Saudi Arabia. Review of transportation system developed in the last three decades including air, land, sea and rail transportation. Problems raised from each mode of transportation were addressed and possible solution were provided. The results indicate that air transportation could provide the necessary needs of the Kingdom of Saudi Arabia in international connections while domestic air transportation provide limited passenger transportation for relatively long distances. This mode is limited to high income people and cannot serve short distances in effective way. Sea transportation could provide the country with freight transport but limited to passengers only in the Golf region or in the red see with some African countries. Road and highway provide the most transportation used by the public but associated with several problems such as environmental pollution, large number of road traffic accident and became the first cause of death in the Kingdom. Bus and car public transportation need essential improvement to meet the demand and save transportation for the public. Rail transportation seems to be the most sustainable transportation in future transportation in the country. Saudi Arabia late pay attention to rail transportation and recently intensive budget invested in rail transportation. Further development in rail transportation in the Kingdom is needed.